Free erythrocyte protoporphyrin its relation to transferrin saturation, serum iron and hemoglobin levels in pregnant women living in district IV, Manila. - Rabuco, Lucila B.
The parameters used in the study of iron-deficiency are percent saturation of transferrin (TSI), serum iron (SeFe) level and hemoglobin (Hb) concentration. The erythrocyte protoporphyrin level which is now well-recognized to the elevated in iron-deficiency has recently been employed together with the above parameters. Pregnancy predisposes women to iron-deficiency and although several studies have been done on this locally, nothing on the measurement of erythrocyte protopporphyrin as a test of iron-deficiency has been reported in Philippine literature. Thus, a study on the erythrocyte protoporphyrin level was done on 592 pregnant women of varying gestational stages. The results revealed that protoporphyrin level exhibited negative correlation with TSI, SeFe levels and Hb concentration. This findings was consistent with those reported in the literature. Using TSI as an index, iron-deficiency was found in 39.6 , 47.3 and 63.3 of pregnant women in the 1st, 2nd and 3rd trimesters respectively. In contrast, only 14.3 , 25.0 and 39.9 of the same groups of women had anemia based on Hb concentration. Among the iron-deficient groups, the protoporphyrin levels ranged from 20.3-342.8 ug/100 ml RBC. In the group without iron-deficiency, the range was 14.3-103.3 ug/100 ml RBC. The mean values obtained for both groups were significantly different from each other. For the control group, 54 apparently health, non-pregnant women were examined. It was found that 27.7 had iron-deficiency while only 9.2 had anemia. The mean value of the erythrocyte protoporphyrin for the non-iron-deficient group was 40.1 ug/100 ml RBC. A mean value of 96.9 ug/100 ml RBC was obtained for the iron-deficient group. This was significantly higher than that of the non-iron-deficient group. To examine its usefulness as a test of iron-deficiency, the percent level of agreement with TSI, SeFe and Hb concentrations was done. High levels of agreement in classifying iron-deficiency states were obtained for the non-pregnant women and in the women in the 1st trimester (83.3 and 83.5 respectively). In spite of the lower percentages of 62.5 and 60.5 seen for the 2nd and 3rd trimesters, it can be concluded that the erythrocyte protoporphyrin level supported the diagnosis of iron-deficiency anemia when taken together with other parameters.